Evaluation of Healthy Eating Index and Children's Diet Inflammatory Index according to asthma severity group - Nevra Koç; Nursena Ersoy; Hülya Yardimci; İlknur Külhaş Çelik; Ersoy Civelek (BMC Pediatrics, 2024)
Abstract Background Diet may contribute to better asthma control in children by impacting the immune and inflammatory pathophysiology. Therefore, this study aimed to investigate differences in nutrient intake, Children’s Dietary Inflammatory Index (C-DII), and dietary quality according to asthma severity. Materials and methods Asthma severity, dietary inflammatory status, and diet quality were assessed in a sample of 202 children with asthma (55.6% males, aged 5–18 years) attending a pediatric allergy outpatient clinic. Asthma severity was evaluated according to the Global Initiative for Asthma criteria and categorized as mild, moderate, or severe. The Children’s Dietary Inflammatory Index (C-DII) and Healthy Eating Index (HEI-2010) were calculated based on information collected by the 24-h dietary recall method. Dietary quality was categorized as poor, moderate, or good diet according to HEI-2010. Results The mean age of the participants was 9.6 ± 3.2 years. Children with severe asthma were younger on average (p < 0.05). Children with mild asthma had significantly higher fiber and iron intake than those with moderate asthma (p < 0.05). C-DII values did not differ significantly according to asthma severity (p > 0.05). Dietary quality was evaluated as moderate in 89.1% of the participants and also showed no difference based on asthma severity. Conclusions These findings suggest that inflammatory status and diet quality may not affect asthma severity in children, highlighting the influence of various genetic and environmental factors on the association between diet and asthma severity. More comprehensive and longitudinal studies are needed to investigate the mechanisms linking diet and asthma.